2006
DOI: 10.1039/b509971b
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the formation of supported bilayers by amphiphilic peptidyl-RNA

Abstract: Amphiphilic peptidyl-RNA conjugates, molecules that mimic natural peptidyl-transfer RNA, are capable of self-assembling on glass substrates as vesicles and supported bilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(9 reference statements)
2
2
0
Order By: Relevance
“…When the reaction was complete, the reaction mixture was filtered and evaporated under vacuum; the yellowish solid formed and crystallized from ethanol is 1 (95% yield). Analytical data ( 1 H and 13 C NMR) are in perfect agreement with those published. 32 Solid Lipid Nanoparticle (SLN) Preparation.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…When the reaction was complete, the reaction mixture was filtered and evaporated under vacuum; the yellowish solid formed and crystallized from ethanol is 1 (95% yield). Analytical data ( 1 H and 13 C NMR) are in perfect agreement with those published. 32 Solid Lipid Nanoparticle (SLN) Preparation.…”
Section: Methodssupporting
confidence: 86%
“…Among these synthetic amphiphiles, micelle-forming polymers are the subject of high interest and are used in therapy for hydrophobic drug formulation. [5][6][7][8][9] More sophisticated amphiphiles such as peptides [10][11][12] or peptidyl-nucleic acid 13 have been shown to form micelles, but their high production costs may be a limiting factor for their commercial use. In the case of amphiphilic peptides, it has been demonstrated that the self-assembly process may take place when the amphiphiles are injected from water to a given physiological milieu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it has recently been shown that both peptide and nucleic acid precursors can be formed in a prebiotic environment from simple building blocks of unified origin, we suggest that synergistic activity such as that demonstrated here may have led to the selection of functional chimeras. Together with other recent results demonstrating structural and functional synergy in NA‐pep systems and also synergy between simple prebiotically relevant molecules from different families, such as NA‐lipid, pep‐lipid, and sugar‐pep, the current study shows the rapid progression in complexity and systems chemistry that would have facilitated a large repertoire of functions.…”
Section: Discussionsupporting
confidence: 77%